Peran Dewan Perwakilan Daerah (DPD) Sebagai Representasi Daerah Di Masa Pandemi - Wasti, Ryan Muthiara (Jurnal Konstitusi & Demokrasi, 2025)
The COVID-19 pandemic has been one of the most challenging phases for all countries affected by it, including Indonesia. The impacts of the COVID-19 pandemic are not limited to the health sector but also extend to other areas such as the economy and society. Given the various impacts of COVID-19 felt by the community, new rules regarding new norms or what is often referred to as the “new normal” have begun to be implemented in various regions. Therefore, law enforcement during the COVID-19 pandemic does not only involve policymakers at the central government level but also requires the involvement of policymakers representing each region to ensure that the aspirations of the community are heard. This is because the impacts of the COVID-19 pandemic felt directly by the community in each region will inevitably vary, so the regulations needed by the community must be able to adapt to the needs at that time. In this regard, the role of the Regional Representative Council (DPD) as a regional representation becomes crucial in conveying the aspirations of the community to ensure that law enforcement aligns with the needs of various regions.